LB007 Intrasaccular flow disruption for ruptured aneurysms: an international multicenter study. (26th July 2022) - Diestro, J; Dibas, M; Adeeb, N; Regenhardt, R; Vranic, J; Guenego, A; Lay, S; Renieri, L; Sundararajan, S; Premat, K; El Namaani, K; Saliou, G; et al.
Abstract : Background: The Woven EndoBridge (WEB) device is a novel intrasaccular flow disruptor tailored for bifurcation aneurysms. We aim to describe the degree of aneurysm occlusion at the latest follow-up and rate of complications of aneurysms treated with the WEB device stratified according to rupture status. Method: Our data was taken from the WorldWideWeb Consortium, an international multicenter cohort including patients treated with the WEB device. Aneurysms were classified into two groups: ruptured and unruptured. We compared clinical and radiologic outcomes of both groups. Propensity score matching (PSM) was done to match according to age, gender, bifurcation, location, prior treatment, neck, height, dome width, daughter sac, incorporated branch, pretreatment antiplatelets, and last imaging follow-up. Results: The study included 676 patients with 691 intracranial aneurysms (529 unruptured and 162 ruptured) treated with the WEB device. The PSM analysis had 55 pairs. In both the unmatched (85.8% vs. 84.3%, p=0.692) and matched cohorts (94.4% vs. 83.3%, p=0.066), there was no significant difference in the adequate occlusion rate at the last follow-up. Likewise, there were no significant differences in both ischemic and hemorrhagic complications between the two groups. There was no documented aneurysm rebleeding after WEB device implantation. Conclusion: There is no significant difference in both the radiologic outcomes and complications between unruptured and ruptured aneurysms. Our findings support the feasibility of treatment of ruptured aneurysms with the WEB device. Disclosures: J. Diestro: None. M. Dibas: None. N. Adeeb: None. R. Regenhardt: None. J. Vranic: None. A. Guenego: None. S. Lay: None. L. Renieri: None. S. Sundararajan: None. K. Premat: None. K. El Namaani: None. G. Saliou: None. M. Möhlenbruch: None. I. Lylyk: None. P. Foreman: None. J. Vachhani: None. V. Župančić: None. M. Hafeez: None. C. Rutledge: None. H. Rai: None. V. Tutino: None. S. Mirshahi: None. S. Ghozy: None. P. Harker: None. N. Alotaibi: None. J. Rabinov: None. J. Spears: None. C. Parra-Farinas: None. A. Patel: None. A. Dmytriw: None.